DEVELOPMENT OF BORDER AREAS AS A GOOD AND PROUD FRONT YARD - Widia Novita Lukitasari WA (Jurnal Ilmu Pemerintahan, 2026)
Border area development constitutes one of Indonesia's national strategic priorities as it is closely related to national sovereignty, security, equitable regional development, and community welfare. Nevertheless, border regions continue to face numerous challenges, including limited infrastructure, inadequate education and healthcare services, geographical isolation, and the underutilization of natural resource potential. This paper aims to analyze border area development as the "front porch" of the nation by focusing on Banda Neira as one of Indonesia's strategic archipelagic regions. The study employs a library research approach by examining relevant laws and regulations, national development planning documents, and previous studies on border area management. The findings indicate that sustainable border development requires an integrated approach encompassing prosperity, security, and environmental sustainability. Furthermore, effective collaboration among the central government, local governments, the private sector, academia, and local communities is essential to strengthen governance based on good governance principles. The development of Banda Neira as a historical, cultural, and marine tourism destination is expected to enhance regional competitiveness while reinforcing its strategic role as the front gateway of the Republic of Indonesia.